1998
DOI: 10.1897/1551-5028(1998)017<0814:pamdot>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Photolytic and Microbial Degradation of 3,5,6-Trichloro-2-Pyridinol

Abstract: Abstract-The photolytic and microbial degradation of 3,5,6-trichloro-2-pyridinol (TCP), a metabolite of the insecticide chlorpyrifos and the herbicide triclopyr, has been investigated. TCP (80 mg/L) was decomposed to nondetectable levels within 2 h of ultraviolet irradiation. Release of 14 CO 2 and chloride ion was observed; however, approximately 60% of the initial radioactivity remained in the solution. Dichlorodihydroxypyridine isomers and reductive dechlorination products were found as intermediate product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Later the same group, on the basis of combined experiments with photolysis and microbial degradation, suggested that TCP was metabolized by a Pseudomonas sp. by a reductive dechlorination pathway (Feng et al , 1998). In this pathway, TCP is first reductively dechlorinated into chlorodihydro‐2‐pyridone, which is further dechlorinated to tetra‐hydro‐2‐pyridone.…”
Section: Microbial Degradation Of Organophosphorus Compoundsmentioning
confidence: 99%
“…Later the same group, on the basis of combined experiments with photolysis and microbial degradation, suggested that TCP was metabolized by a Pseudomonas sp. by a reductive dechlorination pathway (Feng et al , 1998). In this pathway, TCP is first reductively dechlorinated into chlorodihydro‐2‐pyridone, which is further dechlorinated to tetra‐hydro‐2‐pyridone.…”
Section: Microbial Degradation Of Organophosphorus Compoundsmentioning
confidence: 99%
“…ATCC 700113 degraded the reductive dechlorination products of TCP generated by photolysis, suggesting that Pseudomonas sp. ATCC 700113 utilizes a reductive dechlorination pathway in degrading TCP (18). However, we propose that TCP is dechlorinated by oxidative and hydrolytic reactions in strain T6, to generate DHPD.…”
Section: Discussionmentioning
confidence: 85%
“…A reductive dechlorination mechanism was proposed in the TCP degrader Pseudomonas sp. ATCC 700113 (18), which is the well-known metabolic pathway of TCP biodegradation.…”
mentioning
confidence: 99%
“…Although differentiation between microbial and abiotic processes in the degradation of chlorpyrifos to TCP is not clear, further degradation of TCP has been generally considered to occur through microbial processes [2,15,17]. Feng et al [27,28] isolated a bacterium from an agricultural soil that can use TCP as a sole source of carbon and energy under aerobic laboratory conditions. However, degradation of TCP did not occur in the presence of the bacteria in the animalderived effluents collected from the Baker Farm in this study.…”
Section: Discussionmentioning
confidence: 99%